Nursing students’ experiences of health screening in rural areas of southern Turkey: a qualitative study - Ayşegül Ilgaz; Sebahat Gözüm (James Cook University, 2022)
Introduction: Individuals in rural areas live with healthcare disadvantages relating to, for example, access to health institutions, necessary treatments, and healthcare professionals during medical emergencies. The aim of this study was to explore the experiences, beliefs and attitudes of nursing students to identify advantages and disadvantages of health screening in several rural areas in rural Turkey. Methods: Health screening practices with senior nursing students were conducted in six rural areas. A qualitative descriptive study was performed using thematic analysis of open-ended responses to a web-based survey of 34 students aged 18 years and over. This study was conducted in March and April 2020. Results: The practices of nursing students in rural areas included measuring vital signs, body mass index calculation, blood glucose and cholesterol measurement, depression screening, cancer screening and health education. Students undertook various health screening practices in rural health care including colorectal cancer screening, evaluation of scales used in diabetes and depression risk. Characteristics referred to by student nurses as part of public health nursing roles were protector, advocate, supporter, caregiver, coordinator, collaborator, educator, counsellor, researcher, therapist, case manager, leader and care provider. The main themes generated related to student emotions, feedback of screening participants to nursing students, positive nursing characteristics, advantages and disadvantages of doing health screening in rural areas, benefits of working with health professionals to nursing student education, and feedback for nursing educators and researchers. Conclusion: Participants recognised their emotions, and the benefits and advantages of health screening practices, and disadvantages were determined across the themes. Health services should be planned by taking these experiences into account in health screenings to be carried out in rural areas.